As contribuições do modelo de consultoria interna de recursos humanos para o alinhamento entre as pessoas e a estratégia da empresa - Silva, Dirlene Regina da (Universidade do Vale do Rio dos Sinos, 2013)
The present study has as its theme the model of internal human resources consulting. The main objective is to analyze the contributions of this model for the alignment between people and business strategy. The study is a qualitative research, represented by a single case study, conducted in two stages: exploratory and descriptive. The exploratory stage aims to explore the topic and contemplates the view that management experts people have about the model of internal human resources consulting. The stage descriptive presents the case study realized in the Artecola Company. Data were collected through semi-structured interviews and documents, and were analyzed using the technique of content analysis. The theoretical framework used for this study were the authors: Mancia (1997, 2010), Alberton, Mancia and Borba (2009), Orlickas (2012), Gil (2011), Leite et al. (2009) Teixeira et al. (2005), Marras (2011), among others. The main results show that the model of internal human resource consulting associated with policies and practices the management of people contributes to the alignment between people and business strategy, since the model brings people together, facilitates communication between them and thus relaxes the structure of the company and ensures strategic management of people.
Keywords: Consultoria interna de recursos humanos; Gestão estratégica de pessoas; Agregar valor; Foco em resultados; Pessoas; Consulting internal human resources; Strategic people management; Add value; Focus on results; People; ACCNPQ::Ciências Sociais Aplicadas::Administração